When regular is not easy: Cracking the code of Irish orthography. Issue 2 (2nd July 2016) - Stenson, Nancy; Hickey, Tina M.
ABSTRACT: Irish is well-known to be a threatened minority language, which has a number of under-researched features. This article presents an analysis of Irish orthography, based on the most frequent words in a corpus of children's literature in Irish. We identify both basic orthographic rules and a few phonological rules that systematically alter pronunciations from those expected based on the orthographic norms. While comparison of Irish spelling patterns with those in a similar corpus for English confirms a widespread belief that the orthography of Irish is more regular than that of English (the L1 of most beginning readers of Irish), this analysis refutes the commonly accepted corollary assumption that explicit decoding instruction in Irish is unnecessary for learners already literate in English, based on further examination of other features differentiating the two languages. We argue that, despite its greater regularity, Irish spelling is sufficiently complex and distinct from English to challenge learners and require explicit instruction.